Changes in Running Economy During a 65-km Ultramarathon - Scheer, Volker; Vieluf, Solveig; Cramer, Leoni; Jakobsmeyer, Rasmus; Heitkamp, Hans-Christian (Frontiers in Physiology, 2018)
Purpose: Running economy (RE), expressed as oxygen cost (O2 cost) and energy cost of running (Cr) is important in ultramarathon (UM) running as it can help predict race performance. Controversy remains if RE increases, decreases or remains stable in UM running. We examined RE before, during and after a 65km UM. Methods: 15 male UM runners (mean age 45±5.7 years) completed a standard exercise test (mean VO2max 48.8±3.4 ml.kg-1.min-1) for determination of the individual testing speed (60% VO2max: mean speed 9.4±0.7 km/h). This was followed by a 65km UM (elevation +/-1093m) consisting of 3 laps (each 21.7km). Pre and post indirect calorimetry measurements at individual running speed on the treadmill at UM specific slopes (average percentage of positive and negative elevation) at -3%, +3% and level grade were performed in randomized order on a motorized treadmill in the laboratory for calculation of RE. Additionally after each lap testing at +3% took place. Results: The O2 cost, Cr and RER increased significantly pre to post UM (p<0.01). During the uphill running a main effect of distance indicated a gradual, linear increase in O2 cost, F(2,28)=5.81, p<0.01, ηp2=0.29, and Cr, F(2,28)=5.96, p= 0.01, ηp2=0.30. Conclusions: Oxygen cost and energy cost of running increased significantly pre to post UM in all testing conditions as well as during the uphill testing throughout the UM. This is the first study to demonstrate a consistent increase in O2 cost and Cr among a range of different slopes, at individual running speeds and race specific slopes giving further evidence that these measures of RE increase in UM running.